Interference in Atomic Magnetometry. Issue 12 (4th October 2020) - Jiang, Min; Xu, Wenjie; Li, Qing; Wu, Ze; Suter, Dieter; Peng, Xinhua
Abstract: Atomic magnetometers are highly sensitive detectors of magnetic fields that monitor the evolution of the macroscopic magnetic moment of atomic vapors, and opening new applications in biological, physical, and chemical science. However, the performance of atomic magnetometers is often limited by hidden systematic effects that may cause misdiagnosis for a variety of applications, for example, in nuclear magnetic resonance (NMR) and in biomagnetism. In this work, a hitherto unexplained interference effect in atomic magnetometers is uncovered, which causes an important systematic effect to greatly deteriorate the accuracy of measuring magnetic fields. A standard approach to detecting and characterizing the interference effect in, but not limited to, atomic magnetometers is presented. As applications of the work, the effect of the interference in NMR structural determination and locating the brain electrophysiological symptom is considered, and it is shown that it will help to improve the measurement accuracy by taking interference effects into account. Through the experiments, good agreement is indeed found between the prediction and the asymmetric amplitudes of resonant lines in ultralow‐field NMR spectra—an effect that has not been understood so far. It is anticipated that the work will stimulate interesting new researches for magnetic interference phenomena in a wide range of magnetometers and their applications. Abstract : An interference effect is uncovered and characterized in atomic magnetometry. Such an effect provides the first explanation for the hitherto unexplained asymmetry observed in ultralow‐field NMR spectra. Interesting new researches for magnetic interference phenomena are anticipated in a wide range of magnetometers and their applications in biological, physical, and chemical science.